Loop-Mediated Isothermal Amplification Test for Trypanosoma gambiense Group 1 with Stem Primers: A Molecular Xenomonitoring Test for Sleeping Sickness - Zablon K. Njiru; Cecilia K. Mbae; Gitonga N. Mburugu (Journal of Tropical Medicine)
The World Health Organization has targeted Human African Trypanosomiasis (HAT) for elimination by 2020 with zero incidence by 2030. To achieve and sustain this goal, accurate and easy-to-deploy diagnostic tests for Gambian trypanosomiasis which accounts for over 98% of reported cases will play a crucial role. Most needed will be tools for surveillance of pathogen in vectors (xenomonitoring) since population screening tests are readily available. The development of new tests is expensive and takes a long time while incremental improvement of existing technologies that have potential for xenomonitoring may offer a shorter pathway to tools for HAT surveillance. We have investigated the effect of including a second set of reaction accelerating primers (stem primers) to the standard T. brucei gambiense LAMP test format. The new test format was analyzed with and without outer primers. Amplification was carried out using Rotorgene 6000 and the portable ESE Quant amplification unit capable of real-time data output. The stem LAMP formats indicated shorter time to results (~8 min), were 10–100-fold more sensitive, and indicated higher diagnostic sensitivity and accuracy compared to the standard LAMP test. It was possible to confirm the predicted product using ESE melt curves demonstrating the potential of combining LAMP and real-time technologies as possible tool for HAT molecular xenomonitoring.